Netflix and the American Prison Film: Depictions of Incarceration and the New Prison Narrative in Ava DuVernay’s 13th (2016) - Festa, Beatrice Melodia (Hungarian Journal of English and American Studies, 2022)
The essay examines the complexities of America’s penal system through the lens of prison films and the recurrent representations of incarceration on screen. Following an introduction about America’s penal system, Mass Incarceration, and the enforcement of systemic racism through the Prison Industrial Complex, the analysis focuses on the images of confinement in movies. An overview of traditional narratives on prison is offered to highlight the main characteristics of the ambiguous and challenging genre of the prison film, while a closer look at one of its contemporary examples, Ava DuVernay’s 13th (2016), sheds light on how the presence of Netflix and the innovative narrative strategy employed to portray the complexities of confinement represent a new form of prison film—one that abandons a Hollywoodesque approach in favor of a documentaristic strategy, and, through its distribution on Netflix, reaches its target audience. The analysis conclusively demonstrates how Netflix has changed and challenged the way we see prisons on screen, and how, as DuVernay’s docufilm shows, it has posited the tangled question of race so that the viewer can understand the functioning of the modern prison. By way of conclusion, the essay demonstrates that the new prison film, shifting toward distribution on Netflix as a mode of audience registration, clearly manifests a strategy to instruct American public opinion on race and the criminal justice system. (BMF)